Peran Filosofi Pendidikan dalam Menghadapi Transformasi Digital Pembelajaran: Tinjauan Pustaka Sistematis (SLR) - Syahrul Rohmawan; Eva Febrianti; Rohmalita Febrianti; Fitria Anjani; Salma Aulia Lismaya; Nur Cahya (Sumule Indonesia Publishing, 2026)
This systematic literature review investigates how educational philosophy guides the transformation of digital learning through the lens of ethics, humanism, epistemology, and pedagogy. The review was carried out using a PRISMA-informed process. Records for 2015-2025 were collected from Google Scholar using Publish or Perish. Of the 103 records initially identified, 16 duplicates were removed, 87 titles and abstracts were screened, 41 full texts were assessed for eligibility, and 10 studies met the inclusion criteria. The included studies were analysed using thematic synthesis. The findings suggest that educational philosophy provides a normative basis for evaluating digital learning that goes beyond mere technological efficiency. Five major themes emerged. First, educational philosophy grounds ethical decision-making in artificial intelligence, learning analytics, privacy, and algorithmic bias. Second, it maintains the humanistic orientation of education by emphasizing dialogue, dignity, character formation and the teacher's presence. Third, it promotes critical thinking and epistemic awareness in information-rich digital environments. Fourth, it supports digital pedagogy by connecting technological tools to learning goals, curriculum values, and teachers’ roles. Fifth, it provides a critical perspective to tackle digital inequality and unequal access to infrastructure, devices and digital competence. This review finds that digital transformation in education requires more than technical adoption. It needs a strong philosophical grounding to ensure learning is ethical, inclusive, human-centred and socially responsible.